2022
DOI: 10.1155/2022/2264394
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Study of Jian-Gan-Xiao-Zhi Decoction on Nonalcoholic Fatty Liver Disease Based on Integrated Network Pharmacology and Untargeted Metabolomics

Abstract: Jian-Gan-Xiao-Zhi decoction (JGXZ) has demonstrated beneficial effects on nonalcoholic fatty liver disease (NAFLD). However, the mechanisms by which JGXZ improve NAFLD are still unclear. Methods. In this study, we first used a high-fat diet (HFD) to establish a NAFLD rat model to clarify the therapeutic effect of JGXZ on NAFLD. Secondly, we used network pharmacology to predict the potential targets of JGXZ on NAFLD, and then the key targets obtained from network pharmacology were verified. Finally, we used untar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The aforementioned ndings indicate that a signi cant proportion of glycerol phospholipids and their metabolites were altered in the blood of individuals with HUA, and the disturbance of phospholipid metabolism mainly involves phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidylcholine (PC), phosphatidylserine (PS), lysophosphatidylinositol (LPI). These lipid molecules can participate in bio lm formation, cell membrane recognition, and signal transduction [19] . For example, UA can activate LPCs, allowing UA to activate phospholipid remodeling enzyme LPCAT3 in vivo and in vitro and nally catalyze the generation of PCs [18,20] .…”
Section: Elisa Resultsmentioning
confidence: 99%
“…The aforementioned ndings indicate that a signi cant proportion of glycerol phospholipids and their metabolites were altered in the blood of individuals with HUA, and the disturbance of phospholipid metabolism mainly involves phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidylcholine (PC), phosphatidylserine (PS), lysophosphatidylinositol (LPI). These lipid molecules can participate in bio lm formation, cell membrane recognition, and signal transduction [19] . For example, UA can activate LPCs, allowing UA to activate phospholipid remodeling enzyme LPCAT3 in vivo and in vitro and nally catalyze the generation of PCs [18,20] .…”
Section: Elisa Resultsmentioning
confidence: 99%
“…SOD can catalyze superoxide into oxygen and hydrogen peroxide (H2O2) (33). GSH-Px catalyzes the conversion of reduced GSH to oxidized glutathione, protecting cells from disruption and damage caused by peroxide (34). MDA is the last product of lipid peroxidation, and it is an important indicator of body's oxidative stress levels (35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to forming biofilms and recognizing cell membranes, these lipid molecules play a key role in signal transduction as well 21 . The LPCs can be activated by UA, and recombinant lyso-phosphatidylcholine acyltransferase-3 (LPCAT3) can be activated in vitro and in vivo, catalyzing PC generation 19 , 22 . This indicated that uric acid participates in metabolism and biosynthesis.…”
Section: Discussionmentioning
confidence: 99%